Victims no more! communication strategies and action to raise awareness of the United Nations Security Council Resolution 1325, an international law that highlights women's role as peace builders and decision makers - Balleza, Ma. Victoria Cabrera 1962- (2008)
" This study examines the communication strategies on the UN Security Council Resolution 1325 on Women, Peace and Security in the Philippines. It analyzes the gains, gaps and challenges from the existing communication strategies on the Resolution. Additionally, the study assesses the impact of the communication strategies on the awareness level and knowledge of the Resolution among women's organizations and peace advocates in the Philippines. The study employs an innovative data construction method in the form of a forum-workshop in combination with key informant interviews and focus group discussion. It also makes use of new information and communication technologies such as the online chatting protocols Skype and Yahoo Messenger and Internet telephony.The study reveals that there are gaps and challenges from the communication strategies on Resolution 1325 in the Philippines. This has contributed to the lack of awareness of Resolution 1325 among peace and security stakeholders in the country. It also shows that the Resolution is not integrated in the work of many women's organizations and peace advocacy groups in the Philippines. The other factors that explain the non-implementation of Resolution 1325 are the non-integration of women and gender issued in the mandate of peace advocacy groups; the non-engagement of peace advocacy organizations in UN advocacy; and the women's unequal participation in discussion, policy and decision-making processes on peace and security. As its final output, the study recommends a research-based communication campaign on Resolution 1325."
Vita.
"October 2008."
Thesis (M.A. Communication Research)--University of the Philippines, Diliman.
Keywords: United Nations. -- Security Council -- Resolutions; Women and peace -- Philippines; Security, International; Women -- Political activity -- Philippines; Peace-building -- Philippines